Combining Topological and Steric Constraints for the Preparation of Heteroleptic Copper(I) Complexes. Issue 38 (23rd July 2014) - Mohankumar, Meera; Monti, Filippo; Holler, Michel; Niess, Frédéric; Delavaux‐Nicot, Béatrice; Armaroli, Nicola; Sauvage, Jean‐Pierre; Nierengarten, Jean‐François
Abstract Heteroleptic copper(I) complexes have been prepared from a macrocyclic ligand incorporating a 2, 9‐diphenyl‐1, 10‐phenanthroline subunit (M30) and two bis‐phosphines, namely bis[(2‐diphenylphosphino)phenyl] ether (POP) and 1, 3‐bis(diphenylphosphino)propane (dppp). In both cases, the diphenylphosphino moieties of the PP ligand are too bulky to pass through the 30‐membered ring of M30 during the coordination process, hence the formation of C2v‐symmetrical pseudo‐rotaxanes is prevented. When POP is used, X‐ray crystal structure analysis shows the formation of a highly distorted [Cu(M30)(POP)]+ complex in which the POP ligand is only partially threaded through the M30 unit. This compound is poorly stable as the CuI cation is not in a favorable coordination environment due to steric constraints. By contrast, in the case of dppp, the bis‐phosphine ligand undergoes both steric and topological constraints and adopts a nonchelating coordination mode to generate [Cu2(M30)2(μ‐dppp)](BF4)2. This compound exhibits metal‐to‐ligand charge transfer (MLCT) emission characterized by a very large Stokes' shift (≈200 nm) that is not attributed to a dramatic structural distortion between the ground and the emitting states but to very weak MLCT absorption transitions at longer wavelengths. Accordingly, [Cu2(M30)2(μ‐dppp)](BF4)2 shows unusually high luminescence quantum yields for CuI complexes, both in solution and in the solid state (0.5 and 7 %, respectively).